2011
DOI: 10.2298/jsc100823054n
|View full text |Cite
|
Sign up to set email alerts
|

Multi-criteria analysis of soil pollution by heavy metals in the vicinity of the copper smelting plant in Bor (Serbia)

Abstract: This study highlights the consequences on soil pollution of one hundred years of manufacturing in the Copper Mining and Smelting Complex RTB--Bor (Serbia). Soil sediments were taken via a probe from the surface layer of the soil at twelve different measuring points. The measuring points were all within 20 km of the smelting plant, which included both urban and rural zones. Soil sampling was performed using a soil core sampler in such way that a core of a soil of radius 5 cm and depth of 30 cm was removed. Subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 34 publications
4
19
1
1
Order By: Relevance
“…These results suggested that elevated levels of trace elements and intense activity of sulfate-reducing bacteria may account for bad water quality at these sampling sites [28,29]. Metal processing in the Copper Smelter Complex Bor (RTB Bor) relies on an outdated processing technology, i.e., classic pyrometallurgical processing, that uses sulfur dioxide gas (SO 2 ) to produce H 2 SO 4 with less than 50% degree of utilization [30]. The Kriveljska and Bor rivers gather the waste waters from the “Jama Bor” underground mine, industrial waters from the city of Bor, drainage waters from the Veliki Krivelj tailing dam, Cerovo, Krivelj, and Bor open pit mines, and overburden waters from the Saraka stream [26,31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that elevated levels of trace elements and intense activity of sulfate-reducing bacteria may account for bad water quality at these sampling sites [28,29]. Metal processing in the Copper Smelter Complex Bor (RTB Bor) relies on an outdated processing technology, i.e., classic pyrometallurgical processing, that uses sulfur dioxide gas (SO 2 ) to produce H 2 SO 4 with less than 50% degree of utilization [30]. The Kriveljska and Bor rivers gather the waste waters from the “Jama Bor” underground mine, industrial waters from the city of Bor, drainage waters from the Veliki Krivelj tailing dam, Cerovo, Krivelj, and Bor open pit mines, and overburden waters from the Saraka stream [26,31].…”
Section: Resultsmentioning
confidence: 99%
“…Organic pollutants can also induce EISQ variation in aquatic sediments [20]. However, in the Bor area, this enzymatic bioindicator is mainly associated with inorganic pollution since such compounds are known to regulate the physico-chemical properties of water streams in this region [30,32]. …”
Section: Resultsmentioning
confidence: 99%
“…The annual average mean relative air humidity is 73 %, while the average atmospheric pressure is 971 mbar. The prevailing wind is WNW with an average velocity of 0.5 m s -1 ; the wind still period is over 50 % (Nikolić et al, 2010a). DOI: 10.1515/picbe-2017-0006, pp.…”
Section: Environmental Consequences Of One Century Of Copper Productionmentioning
confidence: 99%
“…Due to the fact that the town was built in the near vicinity of the mine, as well as near the location of the copper smelting plant and two further mines close by, the town itself represents a serious environmental hot spot of Serbia and Europe.25 The Bor River (industrial river), representing one of the most polluted rivers in the world, flows into the Timok River, a tributary of the Danube River ( Fig. 1) (Nikolić et al, 2010a).…”
Section: Environmental Consequences Of One Century Of Copper Productionmentioning
confidence: 99%
“…Crete Tsoutsos et al [30] showed how sustainable energy planning can be done by MCA. The analysis of air pollution [31] and soil pollution [32] in an urban area in Serbia was done by Nikolić et al using MCA.…”
Section: • Environmental Reliabilitymentioning
confidence: 99%